2014
DOI: 10.1111/adb.12164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yohimbine on reinstatement of operant responding in rats is dependent on cue contingency but not food reward history

Abstract: Yohimbine is an alpha-2 adrenoceptor antagonist that has been used in numerous studies as a pharmacological stressor in rodents, monkeys, and humans. Recently, yohimbine has become the most common stress manipulation in studies on reinstatement of drug and food seeking. However, the wide range of conditions under which yohimbine promotes reward seeking is significantly greater than that of stressors like intermittent footshock. Here we addressed two fundamental questions regarding yohimbine’s effect on reinsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 81 publications
0
43
0
Order By: Relevance
“…Given that yohimbine-induced reinstatement of food seeking requires activation of D 1 Rs in mPFC (Nair et al, 2011) and that acute stressors, including yohimbine (Chen et al, 2014; Tanda et al, 1996), selectively increase dopamine in the mPFC—an effect that is sensitized in chronically stressed animals (Di Chiara et al, 1999; Gresch et al, 1994)—we speculate that the enhanced yohimbine-induced responding observed in saline + yohimbine rats in Experiment 1 was due to augmented D 1 R activation in mPFC relative to controls. Blockade of D 1 Rs during yohimbine stress may have attenuated the stress-induced changes in dopaminergic transmission in mPFC.…”
Section: Discussionmentioning
confidence: 90%
“…Given that yohimbine-induced reinstatement of food seeking requires activation of D 1 Rs in mPFC (Nair et al, 2011) and that acute stressors, including yohimbine (Chen et al, 2014; Tanda et al, 1996), selectively increase dopamine in the mPFC—an effect that is sensitized in chronically stressed animals (Di Chiara et al, 1999; Gresch et al, 1994)—we speculate that the enhanced yohimbine-induced responding observed in saline + yohimbine rats in Experiment 1 was due to augmented D 1 R activation in mPFC relative to controls. Blockade of D 1 Rs during yohimbine stress may have attenuated the stress-induced changes in dopaminergic transmission in mPFC.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, recent evidence suggests that some of the effects of yohimbine on operant responding may not be related to stress-like effects and may be independent of the history of contingent self-administration of food [12]. Therefore, a main goal of the present study was to extend our previous findings by determining whether the effects of chronic yohimbine on palatable food seeking generalize to a non-pharmacological stressor.…”
Section: Introductionmentioning
confidence: 78%
“…We hypothesize that this is due to engagement of a common pathway involved in food seeking. Indeed, both yohimbine and non-pharmacological stressors strongly activate [29, 30] and selectively increase dopamine release [12, 31] in PFC. The release of dopamine in PFC and the activation of D 1 Rs in general appear to be critical mechanisms underlying food-seeking behavior [16, 17, 19].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that recent data suggest the actions of yohimbine on operant responding not to be primarily due to its stress-like effects on motivation for drug seeking. Chen et al (2015) presented data showing that the dose commonly used for stress-induced reinstatement for alcohol and other drugs of abuse does not induced conditioned place aversion on its own (Chen et al 2015). Furthermore, they show reinstatement to be due to increased cue-reactivity and/or arousal, since increased responding following extinction and yohimbine-induced reinstatement was seen in a group of animals trained using a cue only (and no reward present).…”
Section: Discussionmentioning
confidence: 99%